2020
DOI: 10.18311/ajprhc/2021/26763
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of Breast Cancer and the Practice of Breast Self-Examination in Saudi Women: An Online Survey

Abstract: Breast cancer is a cancer that spreads all over the world, including Saudi Arabia. Early detection requires awareness and knowledge of possible warning signs and effective methods of examination. The study aimed to evaluate the breast cancer knowledge (risk factors, causes, prevention and treatment) and to assess the Breast Self-Examination (BSE) among women in Saudi Arabia, so as to explore possible correlation between education and knowledge and practice of breast cancer. A total of 697 Saudi women, their ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
2
1
0
Order By: Relevance
“…24 Two recent studies have contributed the lack of practice to lack of knowledge in sup-population of females depending on the level of education (Suleiman 2014) 24 and to the lack of sources in Arabic language. 25 This is in agreement with our study, as we found that there is good knowledge regarding the clinical presentation of the disease. We concluded here that the lack of practice is attributed to lack of knowledge regarding risk factors and lack of knowledge regarding the details of clinical examination including the location, proffered time and intervals between examinations.…”
Section: Discussionsupporting
confidence: 93%
“…24 Two recent studies have contributed the lack of practice to lack of knowledge in sup-population of females depending on the level of education (Suleiman 2014) 24 and to the lack of sources in Arabic language. 25 This is in agreement with our study, as we found that there is good knowledge regarding the clinical presentation of the disease. We concluded here that the lack of practice is attributed to lack of knowledge regarding risk factors and lack of knowledge regarding the details of clinical examination including the location, proffered time and intervals between examinations.…”
Section: Discussionsupporting
confidence: 93%
“…Education levels strongly correlated with knowledge, consistent with Allohaibi et al [ 29 ], who found increasing knowledge with higher education levels. Occupation also influenced awareness; workers were more knowledgeable than housewives/students, though housewives showed significantly lower knowledge.…”
Section: Discussionsupporting
confidence: 89%
“…In Saudi Arabia, investigations have scrutinized women's breast cancer literacy levels and willingness to engage in breast self-examination (BSE), unearthing prevalent knowledge voids [7][8][9][10][11]. A startling revelation from a 2022 study indicated that only 4.2% of the participants demonstrated adequate BSE knowledge [9].…”
Section: Introductionmentioning
confidence: 99%